1999
DOI: 10.1002/jlb.65.2.137
|View full text |Cite
|
Sign up to set email alerts
|

The cell biology of leukocyte-mediated proteolysis

Abstract: Leukocyte-derived proteinases have the capacity to degrade every component of the extracellular matrix, and thereby play fundamental roles in physiological processes. However, if the activity of these proteinases is uncontrolled or dysregulated, they have the capacity to contribute to tissue injury that potentially affects every organ in the body. Although there is a substantial literature on structure and activity of these proteinases when they are free in solution, until recently there has been little inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
403
0
9

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 386 publications
(423 citation statements)
references
References 155 publications
(172 reference statements)
11
403
0
9
Order By: Relevance
“…After LPS infusion, the capacity of caseinolysis of PMN neutral proteases and acidic proteases has been shown by Moussaoui et al [50]. PMN are reported to contain acidic proteases such as cathepsins B, C, D or L [54]. These proteases are not at their optimal pH after degranulation since they are in the environment (milk) with a pH tending to neutrality, suggesting that neutral proteases cannot degrade proteins in an extra-cellular way.…”
Section: Caseinolysis By Pmnmentioning
confidence: 97%
See 3 more Smart Citations
“…After LPS infusion, the capacity of caseinolysis of PMN neutral proteases and acidic proteases has been shown by Moussaoui et al [50]. PMN are reported to contain acidic proteases such as cathepsins B, C, D or L [54]. These proteases are not at their optimal pH after degranulation since they are in the environment (milk) with a pH tending to neutrality, suggesting that neutral proteases cannot degrade proteins in an extra-cellular way.…”
Section: Caseinolysis By Pmnmentioning
confidence: 97%
“…During the inflammatory response, the activities of these proteases are significantly increased as reported for collagenase [60], elastase [5,60], cathepsin G only [5] and both cathepsins C and G [60]. The role of these proteases in the degradation of the extracellular matrix is well known [5,54]. Many studies report a high SCC during mastitis with mainly PMN [31].…”
Section: An Increase In Proteolytic Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that the increased capillary permeability at inflammatory foci allows SSL to extravasate (14). Besides, the infiltration of inflammatory cells may actively or passively promote SSL localization, either by taking up liposomes in the circulation and subsequent infiltration into the inflamed tissue, or by facilitating liposome extravasation as a result of leukocyte-mediated tissue inury (16).…”
Section: Introductionmentioning
confidence: 99%